Analisis Kualitas Pelayanan Berbasis Sustainable Marketing Pada UMKM - Feti Fatimah; Wenny Murtalining Tyas (RELASI : JURNAL EKONOMI, 2023)
MSMEs must continue to maintain customer loyalty even though these MSMEs are located in rural areas. MSMEs in rural areas affect the rate of economic growth in rural areas as well as in Balung Lor Village. MSMEs in this village must immediately get up so that the economy in Balung Lor Village will recover after suspended animation due to the Covid 19 pandemic. The purpose of this study is to analyze the quality of services based on sustainable marketing at MSME Restaurants so that MSMEs are able to continue to grow. The Restaurant MSME was chosen because this MSME was very affected by the Covid 19 pandemic. The type of research was quantitative. The population in this study is the consumer of MSME Restaurants in Balung Lor Village. Using Importance Performance Analysis. The average service gap is -0.438, which describes the service that is not as expected by consumers, so it is necessary to improve the quality of services based on sustainable marketing at MSME Restaurants so that consumer loyalty continues to increase.